Knowledge on Stroke among Middle Aged Adult in a Community at Ratuwamai, Morang - Silwal, Suvekshya; Khadka, Sapana; Sah, Bimala Kumari (Tribhuvan University Journal, 2019)
Stroke is a medical emergency also known as Cerebrovascular Accident (CVA) or "brain attack". Nowadays, this health problem is increasing tremendously day by day in developing country like Nepal.This study follows with an objective to assess the knowledge on stroke among middle aged adult. A descriptive cross-sectional study was used to assess the level of knowledge on stroke among (40-65) years of aged group in a community of Ratuwamai, Morang. Non probability purposive sampling method was used to select respondents where sample size was 117. Semi-structured interview questionnaire was used for data collection and data was analyzed with Statistical Package for Social Science (SPSS) version 16.The study showed that among 117 respondents, 62.1% were above 50 years (Mean±SD = 53.53±7.169), 32.9% had achieved secondary level of education, 97.4% gave correct response as stroke is a brain problem, similarly 100% of respondents reported high risk is above 45years of age, 91.5% identified hypertension leading to stroke, 96.6% thought that sudden onset of dizziness as warning signs of stroke. This study found that overall knowledge regarding stroke was average (65.8%). Relationship of ethnicity (p=0.045) and level of education(p=0.000)were found to be associated with level of knowledge. A widespread awareness program is required to improve the knowledge of community people regarding stroke, which in turn might improve the control of risk factors, early treatment and better outcomes.